Quality of Chiretta (Swertia chirayita) in Cultivated and Wild Samples Collected from Different Districts of Nepal - Barakoti, Tanka P; Tiwari, Narendra N; Yonzon, Minoba (Nepal Journal of Science and Technology, 2013)
An experiment under the scaling up project of ARS Pakhribas was conducted to identify quality and compare the cultivated and wild Chiraito (Swertia chirayita) samples collected from eastern, central and western regions hill districts during 2004. This work aimed to identify best sites/ districts for quality production of this important medicinal herb through cultivation and conservation for initiating export of value added quality product in a sustainable way. Processed product is cheaper to send the overseas market as the volume and weight are decreased. Quality analysis is necessary to ensure quality standard of international market in the context of WTO. Assessment of the collected samples was done by quantifying the extract content and analyzing bitter principle in the Herbs Production and Processing Company lab, Kathmandu. The result revealed that extract content and bitter principle percent varied depending upon different agro-eco growing conditions and extraction method. Hot extraction gave more extract of the plant than cold percolation method. Wild samples, in general, contained higher bitter principle than cultivated, whereas extract content was higher in cultivated Chiraito. The international market could be better ensured with such study result. Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 57-62 DOI: http://dx.doi.org/10.3126/njst.v13i2.7715